Extralevator with vs nonextralevator abdominoperineal excision for rectal cancer: the RELAPe randomized controlled trial. (February 2017) - Bianco, F.; Romano, G.; Tsarkov, P.; Stanojevic, G.; Shroyer, K.; Giuratrabocchetta, S.; Bergamaschi, R.; ,
Abstract: Aim: A randomized controlled trial was conducted to test the null hypothesis that there is no difference in circumferential resection margin (CRM) between extralevator abdominoperineal excision (ELAPE) and non‐ELAPE for rectal cancer. Method: This was a multicentre, randomized controlled trial registered as NCT01702116. Patients with rectal cancer involving the external anal sphincter were randomized to ELAPE or non‐ELAPE following neoadjuvant chemoradiation. Randomization was performed according to Consolidated Standards of Reporting Trials (CONSORT) guidelines. The primary end‐point was CRM (in mm), defined as the shortest distance between the tumour and the cut edge of the specimen. Pathologists and centralized pathology were blinded to the patients' study arm. Interrater reliability (IRR) was assessed using Kendall's coefficient. Intra‐operative perforation (IOP) was any rectal defect determined at pathology. Complications were classified using the Clavien–Dindo classification. Participating surgeons were retrained and credentialed. A sample size calculation showed that 34 subjects would provide sufficient power to reject the null hypothesis. Results: Thirty‐four patients underwent the allocated intervention. Seventeen patients treated with ELAPE were comparable with 17 patients treated with non‐ELAPE regarding age, gender, body mass index (BMI), American Society of Anesthesiology (ASA) class and pre‐existing comorbidities. CRM depth (7.14 ± 5.76 mm vs 2.98 ± 3.28 mm, P  =   0.016) and involvement rates (5.8% vs 41.0%, P  =   0.04) were significantly increased in patients treated with ELAPE. The IRR for CRM was 0.78. There were no significant differences in IOP (5.8% vs 11.7%, P  =   0.77) and complication rates (29% vs 29%, P  =   0.97). Conclusions: ELAPE was associated with statistically improved CRM with no difference in IOP and complication rates compared with non‐ELAPE for rectal cancer involving the external anal sphincter.